Modified mRNA-Based Vaccines Elicit Robust Immune Responses and Protect Guinea Pigs From Ebola Virus Disease. (21st December 2017) - Meyer, Michelle; Huang, Eric; Yuzhakov, Olga; Ramanathan, Palaniappan; Ciaramella, Giuseppe; Bukreyev, Alexander
Abstract : We developed 2 novel lipid nanoparticle-encapsulated, nonreplicating RNA-based Ebola virus vaccines encoding glycoprotein with 1-methylpseudoUTP nucleoside modifications and different signal peptides. Vaccination of guinea pigs elicited high Ebola-specific IgG and neutralizing antibodies and conferred complete protection against Ebola virus disease. Abstract: Most current Ebola virus (EBOV) vaccine candidates are based on viral vectors, some of which cause side effects or require complex manufacturing. Modified mRNA vaccines are easily produced, safe, and are highly immunogenic. We developed 2 mRNA vaccines based on the EBOV envelope glycoprotein, which differed by the nature of signal peptide for improved glycoprotein post-translational translocation. The mRNAs were formulated with lipid nanoparticles to facilitate delivery. Vaccination of guinea pigs induced EBOV-specific IgG and neutralizing antibody responses and 100% survival after EBOV infection. The efficacy of our mRNA vaccine combined with preclinical safety data supports testing in clinical studies.